The Correlation Between Knowledge Level and Peer Role in Preventing Unintended Pregnancies Among Adolescents - Yulistanti, Yeni; Handayani, Lulut; Rahmawati, Wiwin Renny (Poltekkes Kemenkes Semarang, 2024)
Background: Adolescence is the phase of transitional growth and development, ranged from 10 and 19 years. The serious issue that can occur among adolescent is unintended pregnancies. Unintended pregnancy not only affects the adolescent's health but also has social and economic impact. Unintended pregnancy can result from casual relationships, peer influences, and inadequate knowledge among adolescents. A high level of knowledge is expected to enhance the role of peers in preventing unintended pregnancy. Peers can play a role in preventing unintended pregnancy by acting as educators, motivators, and role models.Methods: The aim of this research is to describe the level of knowledge and peer role and their relationship as efforts in preventing unintended pregnancies. The research design is a cross estional study involving 200 female adolescents from high schools in Magelang City. The sampling method used is quota sampling. The instruments used are a knowledge questionnaire consisting of 25 questions and a peer role questionnaire consisting of 24 questions, both of which have undergone validity and reliability testing. The statistical test used is the Spearman Rank Test.Results: Respondents with a good level of knowledge amounted to 187 (93.5%). The role as an educator was high among 175 (87.5%), as a motivator among 138 (69%), and as a model among 158 (79%). There is a significant relationship between the level of knowledge and the role as an educator with a p-value of 0.04. However, there is no significant relationship between the level of knowledge and the role as a motivator with a p-value of 0.14, and there is no significant relationship between the level of knowledge and the role as a model with a p-value of 0.42.Conclusion: Knowledge is associated with the peer role as an educator. Peers can provide information about preventing unintended pregnancies, but efforts to prevent unintended pregnancies still need to be enhanced through the peer role as motivators and role models.